Financial Penalties in the Roman Republic : A Study of Confiscations of Individual Property, Public Sales, and Fines (509-58 BC) - Piacentin, Sofia, (Mnemosyne, Supplements ;, 2022)
Private property in Rome effectively measures the suitability of each individual to serve in the army and to compete in the political arena. What happens then, when a Roman citizen is deprived of his property? Financial penalties played a crucial role in either discouraging or effectively punishing wrongdoers. This book offers the first coherent discussion of confiscations and fines in the Roman Republic by exploring the political, social, and economic impact of these punishments on private wealth.